English Vocabulary Learning by Smartphones of Chinese EFL Learners in Thailand - Yu, Fang; Sukying, Apisak (Journal of Modern Learning Development, 2021)
Vocabulary acquisition is essential in the process of English learning. Word knowledge is based on three interrelated aspects (form, meaning, and use), and each aspect incorporates both a receptive and productive dimension. The increasing use of smartphones is starting to influence how students learn and, in particular, how students acquire vocabulary in foreign language learning. Learning vocabulary by using smartphones exceeds classroom learning limitations, enhances communication and interaction between teachers and students, and brings a new platform to college English learning modes in an online environment, particularly during the Covid-19 pandemic. This study investigates the use of smartphones by Chinese students in learning English vocabulary aspects (form, meaning, and use) both receptively and productively. One hundred and thirty Chinese EFL students studying in Thailand participated in an online questionnaire and interview. The findings showed that Chinese EFL participants used smartphones to learn different word knowledge aspects at different speeds. Specifically, participants often used smartphones to learn word form first, followed by the word meaning and, finally, word use. Furthermore, through smartphones, the recognition of a word often occurs before the production of the word. The current study also showed that Chinese EFL participants held a highly positive attitude towards smartphones in vocabulary learning.